Research on Wavelength Algorithm for Cross-Layer Routing in Software Defi ned Satellite Optical Network - Hai LI; Shanghong ZHAO; Yongjun LI; Cong PENG (天地一体化信息网络)
In response to the difficulty of satellite network management and maintenance and the urgent need for large-capacity data transmission, a software-defi ned satellite optical network cross-layer wavelength routing algorithm based on ant colony algorithm (SDNCLRWA) was proposed.The algorithm took delay and available wavelength rate as heuristic functions, and designed a two-stage cross-layer wavelength routing mechanism to reduced routing hops and network congestion rate.First, it was routed in the LEO satellite single-layer network.The MEO satellite network was used for routing only when the routing fails or the routing hop count was too high.The simulation was carried out under the software-defi ned satellite optical network architecture and the results showed that the SDNCL-RWA algorithm proposed was better than the traditional Dijkstra+FF algorithm and the wavelength routing ant colony algorithm (ACO+FF) in terms of network blocking rate and average routing hops.